Analisi Tingkat Kepuasan Pelanggan Terhadap Kualitas Pemasangan Plafon PVC Menggunakan Metode Customer Satisfaction Index (CSI) (Studi Kasus Desa Tanjung Serupa, Kec. Pakuan Ratu, Kab.Way Kanan - Refision Nugroho; Jati Imantoro; Yateno (Jurnal Manajemen DIVERSIFIKASI, 2025)
Marketing is a body that all activities or efforts are carried out in the field of marketing, namely distributing from producers to consumers through marketing. The main actors in ceiling marketing (PVC), namely ceilings that have water-repellent materials or elastic materials, while the parties involved in preparing ceiling raw materials are workers, ceiling installation services, goods transportation services, and parties who assist in marketing them . The type of research used in this research is descriptive and verification research. Verification research is a type of research that aims to test a theory or results of previous research, (Sukmadinata, 2006:5). Using this research method to determine the significant relationship between the variables studied. The Cuctomer Satisfaction Index (CSI) method was used in this study to examine the effect of the dimensions of service quality on customer satisfaction in PVC ceilings. Analysis of overall customer satisfaction was carried out by calculating the value of the Customer Satisfaction Index (CSI). The consumer satisfaction scale commonly used in index interpretation is a scale of 0 to 1. Based on the calculation of the customer satisfaction index, the CSI value for ceiling installation quality gets a score of 72.74% which is in the range of 66 – 80 meaning customer satisfaction with the overall quality of ceiling installation. seen based on the performance and importance of the attributes are in the criteria of "satisfied". with a scale of 66 to 80 that the level of customer satisfaction in Tanjung Sesama Village is generally in the satisfied category, meaning that the customer feels "satisfied" with the quality of the ceiling installation.